Phosphor-doped hexagonal boron nitride nanosheets as effective acid–base bifunctional catalysts for one-pot deacetalization–Knoevenagel cascade reactions. Issue 22 (24th October 2018) - Zhao, Jun; Lin, Baining; Zhu, Yifan; Zhou, Yonghua; Liu, Hongyang
Abstract : Phosphor doping creates well-defined Brønsted acid and base sites on h-BN nanosheets, ensuring the smooth proceeding of deacetalization–Knoevenagel cascade reaction. Abstract : One-pot cascade reactions over metal-free heterogeneous bifunctional catalysts have been attracting increased attention in green chemistry owing to the advantage of process intensification, as well as the elimination of wastes and metal contamination. In this paper, phosphor-doped hexagonal boron nitride nanosheets (BNP) can act as excellent metal-free acid–base bifunctional catalysts for one-pot deacetalization–Knoevenagel cascade reactions. XRD, FT-IR, XPS, and solid NMR characterizations indicate that phosphor was doped into the framework of h-BN mainly at the corner (N2 PO) and bayer (N3 P–OH) sites. The CO2 -TPD and NH3 -TPD characterizations showed that the BNP sample with optimal phosphor-doping amounts simultaneously possessed the highest amount of acid and base sites. When correlated with the catalytic performance, it can be concluded that mainly N3 P–OH acts as the Brønsted acid sites and –BNH2 and N2 PO as the Lewis and Brønsted base sites, respectively. In addition, the good recycling stability and immobilization feasibility on a monolith support confirm its potential in practical applications.